Performance of Maize (Zea mays L.) Varieties and Soil Amendment Strategies for Sustainable Cultivation in Coastal Saline Soils in Bangladesh: Performance of Maize (Zea mays L.) Varieties - Sultana, Sharmin; Ahmmad, Md Shakil; Islam, Md Sanaul (South Asian Journal of Agriculture, 2025)
The increasing pressure on arable land and the expansion of salinity-affected coastal zones emphasizes the need for developing a new production system that can adapt to coastal soils. In this experiment, maize (Zea mays L.) considered as a possible option for coastal soil adaptation. Coastal soils present significant challenges for maize production due to salinity, weak structure, poor drainage, and low nutrient availability, limiting the crop’s growth and yield potential. This study assessed the prospects of maize cultivation in coastal soil through a two-stage experimental approach. A varietal test was first conducted using three maize varieties (V1: Agro Vision, V2: Lal Teer (Hybrid Maize-Sultan), and V3: BARI Hybrid Maize-6) with three replications, evaluating germination, plant height, leaf number, cob number, and yield. The best-performing variety was then selected for a second experiment involving 10 soil amendment and fertilizer treatments (INF, CD1+INF, CD2+INF, CD3+INF, QC+INF1, QC+INF1.5, QC+INF2, SAND1+INF, SAND2+INF, and SAND3+INF), including inorganic fertilizer alone and combinations with cowdung at different rates, quick compost at increasing fertilizer doses, and varying proportions of sand, to improve maize growth and yield in coastal belt soil. Growth and yield parameters were recorded to determine the effectiveness of each treatment in mitigating soil constraints. The varietal test showed that BARI Hybrid Maize-6performed significantly better than Agro Vision and Lal Teer (Hybrid Maize-Sultan), producing greater plant height (88.97 cm vegetative; 168.33 cm reproductive stage) and the highest grain yield (1.51 t ha⁻¹). In the subsequent treatment experiment, combining cowdung with inorganic fertilizer, especially CD3+INF, resulted in the highest growth and yield (plant height up to 181.74 cm, 8.33 cobs per plant, and 3.61 t ha⁻¹ yield). Quick compost plus inorganic fertilizer also improved growth, and sand plus inorganic fertilizer increased yield compared to inorganic fertilizer alone. While inorganic fertilizer alone yielded only 0.88 t ha⁻¹, adding cow dung increased yield 1.5–4 times within one season. The study suggests that BARI Hybrid Maize-6 with cow dung + inorganic fertilizer is a promising option for coastal soils, though further multi-season field trials are recommended. South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 89-99